A positive shift in resting-state functional connectivity between the insula and default mode network regions reflects the duration of illness in gambling disorder patients without lifetime substance abuse. (30th January 2020) - Tsurumi, Kosuke; Aso, Toshihiko; Kawada, Ryosaku; Murai, Toshiya; Takahashi, Hidehiko
Highlights: GD produced a positive shift in insular-DMN functional connectivity during rest. This alteration was exaggerated with longer illness duration. This finding could enhance our system-level understanding of addiction. Abstract: The insula is considered an important structure involved in addiction and in the context of dynamic activity switching between large-scale brain networks, such as the default mode network (DMN) and the central executive network. Although insular-DMN resting-state functional connectivity (rsFC), which could affect such switching, has been examined in substance addiction populations, the results have been inconsistent, partly because of the confounding neural effects of the abused substances. To investigate this subject, using MRI, we examined insular-DMN rsFC in gambling disorder (GD) patients without a history of substance use. We examined rsFC between insular seeds and DMN regions of interest during rest in 23 GD patients and 27 age-, sex-, handedness-, and high education rate-matched healthy control (HC) subjects. We found a positive shift in insular-DMN rsFC in GD patients compared with HC subjects. Furthermore, the connectivity strength between insular seed regions and DMN regions was positively correlated with illness duration in GD patients. This alteration might affect switching between large-scale brain networks, potentially leading to a preoccupation with gambling as well as various types of cognitive impairments. Our results could clarify the controversial findings regarding substance addiction and enhance the system-level understanding of addiction.